45.0k views
11 votes
Solve for p

- 10p + 3(8 + 8p) = -6(p - 4)

User Bcmills
by
5.1k points

2 Answers

4 votes

Answer:

Explanation:

here you go mate

step 1

- 10p + 3(8 + 8p) = -6(p - 4) equation

step 2

- 10p + 3(8 + 8p) = -6(p - 4) simplify by distributing

14p+24=-6p+24

step 3

14p+24=-6p+24 subtract 24 from each sides

20p=0

step 4

20p/20=0/20 divide both sides by 20

answer

p=0

User Rob Moll
by
5.2k points
3 votes

Answer:

  • p = 0

Explanation:

Given expression:

  • - 10p + 3(8 + 8p) = -6(p - 4)

Solving for p:

  • -10p + 24 + 24p = -6p + 24
  • 14p + 24 = -6p + 24
  • 14p + 6p = 24 - 24
  • 20p = 0
  • p = 0
User Xadm
by
6.2k points